FRI0252 Efficacy of Mycophenolate Mofetil (MMF) versus Oral Cyclophosphamide (CYC) on Skin Thickness in The Scleroderma Lung Study II. (15th July 2016) - Khanna, D.; Tashkin, D.; Furst, D.E.; Tseng, C.-H.; Wilhalme, H.; Roth, M.; Kafaja, S.; Volkmann, E.; Elashoff, R.; Clements, P.; ,
Abstract : Background: Mycophenolate mofetil (MMF) has been shown to improve skin thickness, as assessed by the modified Rodnan skin score (mRSS), in patients with diffuse cutaneous SSc (dcSSc) in retrospective analyses of different cohorts (1). In addition, oral cyclophosphamide (CYC) had a favorable impact on mRSS in SLS-I (2). Objectives: Our objectives were to: 1. Assess the impact of MMF and CYC on the mRSS in a randomized controlled trial of MMF vs. oral CYC in patients with symptomatic scleroderma-related interstitial lung disease (SLS II) over 24 months, and 2. Compare the improvement in mRSS in the SLS I vs. SLS II cohorts at 6 and 12 months. Methods: 142 patients with SSc-ILD were randomized in the SLS II. Patients received MMF (≤3 g daily) for two years or oral CYC (≤2 mg per kilogram of body weight) for one year followed by placebo twice daily for an additional year. In addition, we compared the change in mRSS in the dcSSc subset in the SLS-II vs. SLS-I oral CYC (≤2 mg per kilogram of body weight) and matching placebo prescribed for 1 year. Results: The baseline (mean± SD) disease duration was 2.6±1.8 years and mRSS was 14.0±10.6 for CYC and 15.3±10.4 for MMF groups in the SLS II; 58.5% were classified as dcSSc and 42.5% were classified as limited cutaneous SSc (lcSSc). Both treatments were associated with improvement in mRSS over the period of 24 months but there was no statistically significant between 2 groups at any time points in the dcSSc and lcSSc subsets (p>0.05 for all comparisons). The mean improvement in the CYC group was 1.4 vs. 2.0 in the MMF group in the lcSSc subset and 8.0 vs. 6.3 in the dcSSc subset at 24 months. For our second objective, there was no statistical difference in the baseline mRSS scores in the dcSSc in SLS-I (mean disease duration=3.1 years) and SLS-II (mean disease duration=2.5 years) trials (Table). In addition, the change in mRSS at 6- and 12-month period was similar in the SLS-II pooled (MMF+ CYC) and SLS-I CYC groups (Table; p>0.05). In contrast, SLS-II pooled and SLS-I CYC groups showed statistically significant improvement at 12-month period vs. SLS-1 placebo group (p<0.05). Conclusions: In the SLS II, 2 years of daily MMF and 1-year of CYC were associated with clinically important improvements in mRSS in the dcSSc over 24 months. The change in mRSS in the SLS-II paralleled that in the SLS-I CYC group and was significantly superior to the SLS-I placebo group. These data support the use of MMF or CYC for management of skin fibrosis in early dcSSc. References: Le et al Ann Rheum Dis 2011 Tashkin et al NEJM 2006 Acknowledgement: SLS I and SLS II were funded by NIH/NHLBI Disclosure of Interest: None declared